MANAJEMEN SINDROM ULKUS GENITAL PADA KEHAMILAN - Fajriani, Nur Hikmah (Ensiklopedia of Journal, 2025)
Abstract: Genital ulcers during pregnancy are important clinical problems due to their potential effects on both mother and fetus. The most common cause worldwide is genital herpes simplex virus, followed by syphilis, chancroid, granuloma inguinale, and lymphogranuloma venereum.  Early diagnosis and appropriate management are crucial to prevent complications such as neonatal transmission and adverse pregnancy outcomes. This literature review aims to provide a comprehensive overview of genital ulcer syndromes during pregnancy, focusing on etiology, diagnosis, and management strategies based on CDC 2021 and WHO recommendations. Antiviral therapy for genital herpes, penicillin for syphilis, ceftriaxone or erythromycin for chancroid, erythromycin for granuloma inguinale, and erythromycin for lymphogranuloma venereum are the mainstay treatments recommended for pregnant women. Prevention, early screening, and safe delivery planning remain key strategies to reduce maternal and neonatal morbidity.Keywords: Genital ulcer, pregnancy, management, sexually transmitted infection